Differences in livor mortis in Wistar rats due to organophosphate induction and normal mortality: A randomized experimental study - Nugroho, Novianto Adi; Sena, Muhammad Shokhiful Wafa Arya Wida; Suwandono, Adji (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Pesticide intoxication, a significant global health issue, particularly in developing nations, is often caused by the most toxic pesticides, organophosphates. These substances activate the sympathetic and parasympathetic nervous systems, producing a characteristic livor mortis. It is a secondary sign of death that can be used to estimate the time and cause of death. Objective: This study aims to determine the difference in livor mortis due to organophosphate poisoning and ordinary death (decerebration) using Wistar rats.Methods: From March to April 2023, we conducted an experimental study with a posttest-only control group at the Laboratory of Animal Experiments, Faculty of Medicine, Sebelas Maret University. We used 32 male Wistar rats weighing 150-200 g, divided into control and test groups. The test group received organophosphate diazinon 1.16 ml through a nasogastric tube, while the control group was decerebrated. The data was processed with univariate analysis and an independent t-test.Results: There was a significant difference in the appearance and the persistence time of livor mortis between the control and test groups (p < 0.05). The color of livor mortis in the control group was purplish blue, while in the test group, it was reddish to blackish blue. Most of our samples displayed a distribution of livor mortis in the abdominal and dorsal regions, with a some displaying an abdominal distribution only.Conclusion: Our study reveals significant differences in the appearance and persistence time, as well as the color and distribution of livor mortis between decerebrated and organophosphate-induced dead rats.